Evaluasi Program Pembelajaran Bahasa Arab di SMP IT Nurul Islam Tengaran - Ainy Faizah (LISANIA: Journal of Arabic Education and Literature, 2019)
The purpose of this research was to evaluate the teaching and learning program for Arabic language at Integrated Islamic Junior High School of Nurul Islam Tengaran, based on the quality of lesson planning, the process of teaching and learning activities and the assessment of Arabic lesson. This was an evaluation research by using Countenance Stake model, with descriptive quantitative approach. This research was conducted at Integrated Islamic Junior High School of Nurul Islam Tengaran, putting teachers and students as research subjects. In collecting data, the researcher uses observation, questionnaires, and documentation. The instruments of collecting data for this research have been validated. Instruments for observation and questionnaires have also been estimated to be reliable. After conducting the analysis, the instruments were stated to be valid and reliable so they could be used as a measuring tool in this research. Data analysis technique used for the research was descriptive quantitative. The result of this research showed that (1) the completeness of components in the lesson plan of Arabic language is very good, meanwhile its concordance with the syllabus is in a good category (2) the teaching and learning activity of Arabic language is good, (3) the assessment of Arabic language, is also good, and (4) the learning outcomes of learners have met the passing grade (KKM).